2008
DOI: 10.1063/1.2826376
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of ice in reverse micelles

Abstract: The ultrafast vibrational dynamics of HDO : D 2 O ice at 180 K in anionic reverse micelles is studied by midinfrared femtosecond pump-probe spectroscopy. Solutions containing reverse micelles are cooled to low temperatures by a fast-freezing procedure. The heating dynamics of the micellar solutions is studied to characterize the micellar structure. Small reverse micelles with a water content up to approximately 150 water molecules contain an amorphous form of ice that shows remarkably different vibrational dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 42 publications
7
34
0
Order By: Relevance
“…Bakker and coworkers calculated the relative fraction of shell and core water in anionic AOT or cationic CTAB RMs and observed a size dependence of orientational dynamics on the distance from the interface [145][146][147]. On the basis of these results, the authors considered that all water molecules encapsulated in RMs, regardless of their spatial location inside the micellar pool, suffer modification of their vibrational relaxation rate according to the alteration of the H-bond network.…”
Section: Models For Molecular Dynamics Of Water In Restricted Volumementioning
confidence: 99%
“…Bakker and coworkers calculated the relative fraction of shell and core water in anionic AOT or cationic CTAB RMs and observed a size dependence of orientational dynamics on the distance from the interface [145][146][147]. On the basis of these results, the authors considered that all water molecules encapsulated in RMs, regardless of their spatial location inside the micellar pool, suffer modification of their vibrational relaxation rate according to the alteration of the H-bond network.…”
Section: Models For Molecular Dynamics Of Water In Restricted Volumementioning
confidence: 99%
“…11,12 Amorphous ice encapsulated via the hydrogen-bonded polar heads of AOT molecules was reported to form for relatively small micelles (150 water molecules in the core) at 180 K, whereas the disintegration of larger micelles in the size range of 10−500 nm to release larger ice structures was observed. 13 Recently, Suzuki and Yui demonstrated that the combination of a small sample cell volume and rapid cooling prevents water shedding; metastable cubic ice was detected in AOT reverse micelles with a radius below 2.1 nm. 14 In this work, we aimed to construct switchable reverse micelles based on an azobenzene-containing photoswitch.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several works showed that water is expelled from the micellar water core (water shedding) at subzero temperatures, including a CTAB/water/chloroform- d system. This phenomenon can be suppressed by the fast cooling of reverse micelle solutions at sufficiently low temperatures. , Amorphous ice encapsulated via the hydrogen-bonded polar heads of AOT molecules was reported to form for relatively small micelles (150 water molecules in the core) at 180 K, whereas the disintegration of larger micelles in the size range of 10–500 nm to release larger ice structures was observed . Recently, Suzuki and Yui demonstrated that the combination of a small sample cell volume and rapid cooling prevents water shedding; metastable cubic ice was detected in AOT reverse micelles with a radius below 2.1 nm …”
Section: Introductionmentioning
confidence: 99%
“…39 The temperature dependence of the vibrational lifetime has been explored, 40 its spectral features, 38,39 its dilution-dependence as well as its anisotropy 41 and the dynamics of ice in reverse micelles. 42 One intriguing observation of previous pump-probe experiments were the extreme asymmetry in linewidth between the 0-1 and 1-2 transitions of the OH vibrator of HOD/D 2 O. 38,39 The 1-2 transition, which is reached only in a nonlinear experiment, has an exceptionally broad linewidth of ≈350 cm −1 , comparable with that of liquid water, while that of the 0-1 transition is much narrower with ≈50 cm −1 .…”
Section: Introductionmentioning
confidence: 99%